Introduction to Gas Hydrates - Bavoh, C.B. (Springer Verlag, 2020)
The increasing risk of gas hydrates in flow assurance, and itsÂ recent advances in the potential application of desalination, gas separation, transportation, and storage, demand new and much more efficient additives. The use of chemical additives to manage hydrate formation inÂ flow assurance and promote hydrate application technologies is the best and practicable method. However, new additives are been developed to successful promote hydrate-based technologies in the near future. Herein,Â recent gas hydrate additives are comprehensivelyÂ discussed, alongside their modelling successes. In this chapter, a brief background and general introduction to gas hydrate formation processes and structures are described. The challenges associated with gas hydrates, as well as their potential applications, are also explained. Recent gas hydrate experimental apparatus and procedures are also detailed in this chapter. In addition, a general description of gas hydrate thermodynamics and kinetic modes is also provided. Finally, this chapter provides the necessary fundamental information needed to understand the subsequent chapters. Â© 2020, Springer Nature Switzerland AG.